The Role of Emotion Regulation and Moral Identity in Teachers’ Prosocial Behavior in Inclusive Schools - Isrida Yul Arifiana; Muhammad Ghazali Bagus Ani Putra; Meizola Leviana; Intan Nuraini Rahmawati; Galih Iftikhar (Journal of Educational Studies, 2026)
Prosocial behavior among teachers is influenced by factors such as emotion regulation and moral identity. This study aims to examine the relationships among emotion regulation, moral identity, and prosocial behavior among teachers in inclusive schools. The research employed a quantitative, non-experimental, correlational design. A total of 110 teachers from inclusive schools in East Java participated in this study, selected through convenience sampling. Data were collected using the Emotion Regulation Questionnaire (ERQ), the Self-Importance of Moral Identity Scale, and the Prosocialness Scale for Adults (PSA). Data analysis was conducted using multiple linear regression. The results showed that emotion regulation and moral identity are simultaneously significantly related to prosocial behavior. Both emotion regulation and moral identity were found to have a positive, significant relationship with prosocial behavior. The coefficient of determination indicated that both variables accounted for 20.8% of the variance in prosocial behavior. These findings suggest that teachers’ ability to manage emotions and internalize moral values plays an important role in fostering prosocial behavior. Strengthening emotional and moral aspects is essential to support positive social interactions in inclusive educational settings.